2017
DOI: 10.1155/2017/7460457
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Analysis for a Fluid-Loaded, Simply Supported Plate Covered by a Damping and Decoupling Composite Acoustic Coating

Abstract: This work presents a vibroacoustic response model for a fluid-loaded, simply supported rectangular plate covered by a composite acoustic coating consisting of damping and decoupling layers. The model treated the damping layer and base plate as a unified whole under pure bending moments and the decoupling layer as a three-dimensional, isotropic, linear elastic solid. The validity of the model was verified by both numerical analysis and experiments and was shown to accurately extend previous studies that were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was shown that the wave reflection produced by the stiffeners changed the dispersion relationship and caused the panel to be excited in a coincidental manner by incident sound waves, at frequencies below the critical frequency. Additionally, Yuan et al [7] numerically and experimentally studied the vibroacoustic response of a fluid-loaded, simply supported rectangular plate covered by a composite acoustic coating. They found that only when the loss modulus of the damping layer was sufficiently high and the stiffness of the decoupling layer was sufficiently low, the system can provide an excellent vibration isolation and noise reduction effect.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the wave reflection produced by the stiffeners changed the dispersion relationship and caused the panel to be excited in a coincidental manner by incident sound waves, at frequencies below the critical frequency. Additionally, Yuan et al [7] numerically and experimentally studied the vibroacoustic response of a fluid-loaded, simply supported rectangular plate covered by a composite acoustic coating. They found that only when the loss modulus of the damping layer was sufficiently high and the stiffness of the decoupling layer was sufficiently low, the system can provide an excellent vibration isolation and noise reduction effect.…”
Section: Introductionmentioning
confidence: 99%